RECOGNIZING ETHNOMATHEMATICS IN WAU KITE AND CORAK-RAGI OF TENUNMELAYU FROM KEPULAUAN RIAU PROVINCE AND USING ITS POTENTIALS TOWARDS LEARNING OF SCHOOL MATHEMATICS - FEBRIAN, FEBRIAN (Sriwijaya University Learning and Education International Conference, 2016)
Ethnomathematics proposes the idea of mathematics that develops informally incultural aspects of humanâs life.Mathematics is utilized through some daily activitiessuch as grouping, counting, measuring, designing, playing, locating, etc. For specificgroup of people, mathematical activities can uniquely exist and develop. Hence,ethnomathematics can obviously be subject to diversity since it relies on culture ofspecific groups. The idea of ethnomathematics is promising to learning practice ofschool mathematics for at least two reasons. First, it can provide the context oflearning which is undeniably familiar for learners living in specific area. Second, itenables the reinvention of relevant mathematical concepts which are alreadyarranged formally in school curriculum. Kepulauan Riau province, one of provincesin Indonesia, has rich melayu culture that spreads across the entire islands. Wau kiteand tenun melayuare the examples of many cultural items originating fromKepulauan Riau province. The making of Wau kite utilizes mathematical activityand precision to ensure the kite is fully functioning to be played and flown. Tenunmelayu displays beautifully arranged geometrical patterns called corak-ragi that arecreated by particular technique that involves mathematics. This ethnography basedqualitative study discovers the ethnomathematics behind the creating of Waukiteandcorak-ragioftenun melayu. The data is obtained through interviewandliterature study. Both data are triangulated to get a fuller information. Theanalysis is qualitatively described to deliver attention to two main analysis:etnomathematics domain analysis and ethnomathematics taxonomy analysis on Waukiteandcorak-ragi oftenun melayu. The study indicates that creating of Wau kiteheavily utilizes the length measurement which is a basic topic in schoolmathematics. Modelling of linear function-equation are other topics that can bereinvented. The creating ofcorakoftenun melayu and its variety applies the techniquewhich is familiar to relevant mathematics topic in school such as transformationgeometry (reflection, translation, rotation, and dilation). Other relevant concepts aresymmetry, and transformation composition.